Relationship between Financial Development and Carbon Emission in Indonesia - Sari, Yollit Permata; Akbar, Urmatul Uska; Yeni, Isra; Anis, Ali (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
Financial development is considered as one of the important factors influencing the quality of environment through the consumption of carbon emissions. This study aims to explain the influence of the development of the financial sector on carbon emissions in Indonesia from 1991 to 2020. This research was conducted through a literature study of data that has been published by the world bank and bank Indonesia. The results of the study using multiple linear regression found that of the 6 indicators used, 3 of them found that there was a significant relationship between the development of the financial sector and carbon emissions. The three indicators are Domestic credit provided by the financial sector, Domestic credit to private sector and Domestic credit to private sector by banks. The three variables are significant with values ​​of 0.000, 0.001 and 0.039. Meanwhile, the other 3 variables, namely market capitalization, stock traded and foreign direct investment, are not significant in influencing carbon emissions. Government policies are expected to encourage the financial sector to benefit the environment such as encouraging projects that are more environmentally friendly.